漸増負荷下における自転車エルゴメータ駆動時の外側広筋と大腿直筋の筋活動変曲点と換気性作業閾値の時間的関係 - SASAKI Kentaro; 木村 剛; 野口 雅弘; 小島 聖; 樋口 博之 (理学療法学, 2016)
Purpose: This study was designed to compare the appearance time of the ventilator threshold (VT) point and the electromyographic threshold (EMGT) as manifested by a non-linear increase in the activity of the vastus lateralis (VL) and rectus femoris (RF) muscles during ramp cycling exercise in young and elderly males.Methods: Ten healthy young male and ten community dwelling elderly male participated in this study. Subjects performed cardiopulmonary exercise testing with an expiratory gas analyzer and surface electromyography to evaluate muscle activities of the VL and RF during ramp exercise. The appearance time of the EMGT was calculated employing linear regression analysis.Results: In the young group, there was no difference in the appearance time of the EMGT between VL and RF. These two EMGT appearance times were significantly later than the VT point. In the elderly group, the EMGT appearance time for VL was significantly earlier than the RF and VT point, and the increase in the slope of the regression line for VL was significantly decreased after EMGT. The slope after EMGT for RF was not significant as compared to that before EMGT.Conclusion: In the young group, the appearance of EMGT was attributed to increased recruitment of fast twitch motor units that would presumably be triggered by the increase in anaerobic metabolism. In the elderly group, the increase in the slope of the regression line after EMGT for VL was blunted, possibly indicating delayed muscular fatigue in VL resulting from the activation of another muscle group, i.e. one other than the knee extensors. 【目的】自転車エルゴメータ駆動時の外側広筋（以下，VL）と大腿直筋（以下，RF）の筋活動変曲点（以下，EMGT）と換気性作業閾値（以下，VT point）の時間的関係を明らかにする。【方法】健常若年男性10 人と地域在住高齢男性10 人を対象とし，表面筋電計で計測したVL とRF の活動推移から折れ線回帰を用いてEMGT の時間を求めた。【結果】若年群ではVL，RF のEMGT はともにVT point よりも遅れて出現した。一方，高齢群のVL ではRF およびVT point よりも早期に出現したが，EMGT を境に回帰直線の傾きは有意に低下した。【結論】若年者では，無気的代謝が優位となることで運動単位の追加リクルートが生じ，EMGT が出現することが示唆された。それに対して，高齢者のVL のEMGT は有気的代謝優位の中で出現しており，EMGT を境とした筋活動増加勾配の低下は膝伸展筋以外の筋活動によってVL の疲労を先延ばししている可能性が考えられた。